Penghindaran Pajak, Laporan Keberlanjutan, Corporate Governance Dan Nilai Perusahaan: Dimoderasi Ukuran Perusahaan - Nungki Alfiana (Jurnal Literasi Akuntansi, 2021)
Purpose: This study aims to prove the effect of tax avoidance, sustainability reporting, corporate governance and firm value: firm size as a moderating variable. Method: Manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020 are the samples used in this study. Sampling used purposive sampling method and produced 147 sample data. This research technique uses multiple linear analysis and moderated regression analysis. Finding: The results show that tax avoidance has no significant positive effect on firm value, sustainability reports have a positive effect on firm value and corporate governance has no effect on firm value. Firm size can moderate the effect of tax avoidance on firm value. Firm size can strengthen the positive influence of sustainability reports on firm value. Firm size cannot moderate the influence of corporate governance on firm value. Novelty: The novelty of this research, the researcher adds a moderating variable of firm size and different time periods.